IMPLICATIONS OF THE NORTH SUMATRA MUI FATWA ON TALAQ OUTSIDE THE COURT: Harmonization of Islamic Sharia and Positive Law in Indonesia - Syahputra, Akmaluddin; Yazid, Imam; Wandasari, Opi (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2025)
Out-of-court divorce is a practice still often found in Indonesia, despite being contrary to positive laws, such as Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI). This study aims to analyze the legal implications of talaq outside the court from the perspective of the Fatwa of the Indonesian Ulema Council (MUI) of North Sumatra. With a normative juridical approach, this study explores the legal provisions of talaq in Islamic law, the relevance of fatwa to laws and regulations, and its impact on legal certainty and the protection of the rights of wives and children. Data was obtained through document studies of MUI fatwas, regulations, Islamic legal literature, and related academic studies. The results of the study show that the fatwa of the North Sumatra MUI recognizes the validity of talaq outside the court from a religious perspective, provided it meets the requirements of Sharia, but still recommends reporting it to the religious court to ensure legal certainty. This fatwa educates the public not to impose talaq carelessly and ensures the rights of the parties involved, such as alimony, custody, and the distribution of common property. The legal and social implications of this fatwa reveal a fundamental distinction between Islamic law and positive law, which can impact the protection of family rights. By applying the theory of maqashid shari'ah, this study concludes that the MUI fatwa aims to harmonize Islamic shari'ah values with state law in order to achieve the benefits of society.